Goethes Erzählwerk: Interpretationen - Lützeler, Paul Michael; McLeod, James E. (Reclam, 1985)
Literaturangaben
Hier auch später erschienene, unverändert Nachdrucke
Keywords: Aufsatzsammlung; Konferenzschrift; Epik; Goethe, Johann Wolfgang von